Withhold Release Orders: Firm Behavior Regarding Compliance on Forced Labor and Business Outcomes in the Malaysian Palm Oil Industry - Zhou, Jie. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Economics.; Advisor: Drusilla Brown.; Committee: Jenny Aker.; Keyword: Economics.